An ultra-sensitive luteolin sensor based on Co-doped nitrogen-containing carbon framework/MoS2−MWCNTs composite for natural sample detection. (10th January 2023) - Wang, Yilin; Ni, Meijun; Chen, Jia; Wang, Chenxi; Yang, Yaqi; Xie, Yixi; Zhao, Pengcheng; Fei, Junjie
Highlights: It is the first time to synthesize Co@NCF/MoS2 −MWCNTs nanocomposites. The Co@NCF/MoS2 −MWCNTs has excellent electrocatalytic activity for luteolin. The sensor has ultra-low limit of detection and wide linear range for luteolin. The sensor shows outstanding performance in the analysis of natural samples. Abstract: As a common antioxidant and antimicrobial agent in plants, luteolin has a variety of pharmacological activities and biological effects, the ability to specifically bind proteins and thus inhibit novel coronaviruses and treat asthma. Here, Co doped nitrogen-containing carbon frameworks/MoS2 −MWCNTs (Co@NCF/MoS2 −MWCNTs) nanocomposites have been synthesized and successfully applied to electrochemical sensors. X-ray photoelectron spectroscopy, scanning electron microscopy and X-ray diffraction were used to examine the morphology and structure of the samples. Meanwhile, the electrochemical behavior of Co@NCF/MoS2 −MWCNTs was investigated. Due to its excellent electrical conductivity, electrocatalytic activity and adsorption, it is used for the detection of luteolin. The Co@NCF/MoS2 −MWCNTs/GCE sensor can detect luteolin in a linear range from 0.1 nM to 1.3 μM with a limit of detection of 0.071 nM. Satisfactory results were obtained for the detection of luteolin in natural samples. In addition, the redox mechanism and electrochemical reaction sites of luteolin were investigated by the scan rate of CV curves and density functional theory. This work demonstrates for the first time the combination of ZIF-67-derived Co@NCF and MoS2 −MWCNTs as electrochemical sensors for the detection of luteolin, which opens a new window for the sensitive detection of luteolin. Graphical abstract: Image, graphical abstract